Factors and determinants associated with prevalence of anaemia in adults in Karachi, Pakistan - Bano Channar, Husan; Laghari, Zulfiqar Ali; Ali, Ayaz; Din, Ikram (Journal of the Pakistan Medical Association, 2023)
Objective: To assess the demographic and dietary factors associated with the prevalence of anaemia in multi-ethnic urban settings. Method: The cross-sectional community-based survey study was conducted from August 2020 to May 2021 in Karachi East district, and comprised healthy adults of either gender aged 20-60 years. Data was collected using a pretested questionnaire. Besides, 4ml sample of whole blood was taken from each participant for haematological analysis. Data was analysed using SPSS 23. Results: Of the 416 subjects, 269(64.7%) were males and 147(35.3%) were females, while 334(80.3%) were aged <30 years and 82(19.7%) were aged >30 years. Anaemia was found in 92(22.1%) subjects. Female gender, lower and middle socioeconomic class, nuclear family type, habit of meal-skipping, and infrequent consumption of meat, sweets and milk were all linked to anaemia (p<0.05). Conclusion: Less than a quarter of the sample was found to be anaemic. Steps should be taken to address the identified causes of anaemia. Key Words: Anaemia, Prevalence, Risk factors, Urban, Karachi.